Comparing Traditional and Crowdsourcing Methods for Pretesting Survey Questions. (October 2016) - Edgar, Jennifer; Murphy, Joe; Keating, Michael
Cognitive interviewing is a common method used to evaluate survey questions. This study compares traditional cognitive interviewing methods with crowdsourcing, or "tapping into the collective intelligence of the public to complete a task." Crowdsourcing may provide researchers with access to a diverse pool of potential participants in a very timely and cost-efficient way. Exploratory work found that crowdsourcing participants, with self-administered data collection, may be a viable alternative, or addition, to traditional pretesting methods. Using three crowdsourcing designs (TryMyUI, Amazon Mechanical Turk, and Facebook), we compared the participant characteristics, costs, and quantity and quality of data with traditional laboratory-based cognitive interviews. Results suggest that crowdsourcing and self-administered protocols may be a viable way to collect survey pretesting information, as participants were able to complete the tasks and provide useful information; however, complex tasks may require the skills of an interviewer to administer unscripted probes.